A study of the reaction of four grass species -perennial ryegrass (Lolium Perenne L.), timothy (Phleum pratense L.), cocksfoot (Dactylis glomerata L.) and browntop (Agrostis tenuis sibth.) to an artificial treading treatment - Lancashire, J. A. (Massey Agricultural College, 1961)
The dependence of New Zealand's economy upon grassland has frequently been emphasized. The main features of the pastoral farming systems are; high production pastures, grass/clover combinations, mineral fertilisers, and all-the-year outdoor grazing at relatively high stocking rates (Sears, 1959). Corkill (1957) has demonstrated the role of pasture plant breeding and seed certification. Sears (1953) has shown the importance of pasture top-dressing, the grazing animal, and white clover in the improvement of soil fertility. However, many other methods of increasing the production and utilisation of herbage are under investigation (Evans, 1960). In general, grazing techniques have been based on a rotational system for it was believed that this method had important advantages over continuous grazing systems (Levy, 1950). However, the work of McMeekan (1960) and Freer (1960) with dairy cows, and Lambourne (1956) with sheep, showed that wide differences in grazing technique have comparatively little effect on yield/acre of pasture and stock. The production efficiency was mainly dependent on a high stocking rate. [FROM INTRODUCTION]
Keywords: Pastures; Research; Effect of soil compaction on plants; Grasses; Varieties